Nīshāpūrī Scholars in The Formation of Sunnī Scholarship in The Eleventh Century - Mohammad Syifa Amin Widigdo (Al-Jami'ah Research Centre, 2017)
The role of Nīshāpūrī medieval scholars in the tenth-eleventh century in the formation of Sunnī orthodoxy has been rarely discussed. The existing scholarship focuses primarily on the local history of Nīshāpūr and other parts of eastern Muslim world or emphasizes more on the contribution of Baghdādī scholars in the light of the formation of Sunnī legal schools, which in turn is deemed as Sunnī orthodoxy, than their counterpart in Nīshāpūr and other cities in the east. Therefore, this paper attempts to show how Muslim scholars from Nīshāpūr contributed to the advancement of Sunnī scholarship in the fifth/eleventh century through a closer study of intellectual strategies developed and employed by Nīshāpūrī scholars to cope with their local challenges. They built intellectual networking and attempted to integrate legal and theological scholarship in Islamic scholarship to deal with their local problems, which interestingly shaped their distinctive contribution in the light of Sunnī scholarship tradition. By means of this attempt of intellectual networking and harmonizing legal scholarship (fiqh) and theological scholarship (kalām), they were not only able to tackle local problems but also equipped with intellectual means to push doctrinal boundaries within Sunnī scholarship in the fifth/eleventh century.[Peran ilmuwan Nīshāpūr abad pertengahan dalam pembentukan ortodoksi Sunni di abad 10 – 11 masehi masih jarang dibahas. Kebanyakan sarjana yang ada lebih banyak memperhatikan sejarah lokal Nīshāpūr dan bagian lain dari dunia muslim di timur atau menekankan pada kontribusi sarjana asal Baghdād dimasa puncak formasi mazhab Sunni, dimana lebih sering dianggap sebagai Sunni ortodoks daripada kawan mereka di Nishāpūr dan kota lain di timur. Oleh karena itu, artikel ini berusaha untuk menunjukkan bahwa sarjana muslim dari Nishāpūr berkontribusi pada pengembangan pemikiran Sunni di abad pertengahan melalui kajian mendalam pembangunan strategis intelektual dan karya dari sarjana Nishāpūr dalam mengatasi tantangan lokal. Mereka membangun jaringan intelektual dan berusaha mengintegrasikan hukum dan teologi dalam Islam dengan masalah lokalitas, yang mana kontribusi khasnya berpengaruh dalam tradisi teologi Sunni. Melalui usahanya ini, jaringan intelektual dan harmonisasi fiqh dan kalam, mereka tidak hanya mengatasi persoalan lokal tetapi juga melengkapinya dengan seperangkat intelektual untuk mendorong batas-batas dalam tradisi Sunni di abad pertengahan.]